Taxonomic note on Scythris pangalactis Meyrick 1933, with the description of a new species from Iran and a new synonymy (Lepidoptera, Gelechioidea, Scythrididae) - D’entrèves, Pietro Passerin; Bengtsson, Bengt Å.; Roggero, Angela (Zootaxa, 2012)
The taxonomic position of Scythris pangalactis and its synonymy with S. pelinaula is discussed. A new species is describedfrom SE Iran, S. tridentata Passerin d’Entrèves & Roggero sp. nov. The S. tridentata species-group is established with the redescription of S. pelinaula. A lectotype for S. pangalactis is selected.